High-Strength Concretes with Use of Ashes and Slag Waste of Circulating Fluidized Bed Boilers for Road Products - Ahmednabiev, Rasul; Demchenko, Oksana; Bondar, Liudmyla; Popovych, Nataliia (International Journal of Engineering and Technology, 2018)
The results of studies on the influence of ash slag from circulating fluidized bed boilers on the heavy concretes properties are presented. Portland cement PPC 500 N, sand with the fineness modulus M = 1.05, 5-10 mm fractions granite macadam, â€œFluid Premiaâ€“196â€ plasticizer were used in the studies. The studies were carried out using mathematical planning of the experiment.Mechanical properties of concretes have been studied using ordinary hydraulic presses, and in the study of freeze-thaw resistance, the dilatometric method was applied, and the water absorption in a vacuum chamber is taken for the concrete porosity criterion. It is established that with increasing a degree of sand replacement with ash-slag, the strength properties of concrete decrease by 3-10% in comparison with concretes not-containing slag. However, the use of a plasticizer permits to compensate the reduction and to obtain high strength concretes.As a result of the research, the optimal heavy concretes compositions with the use of ash slag to manufacture small products for road pavements have been determined.Â